A new image encryption based on bit replacing, chaos and DNA coding techniques - Yousif, Sura F.; Abboud, Ali J.; Alhumaima, Raad S. (Multimedia tools and applications, 2022)
Millions of confidential images are transmitted every day by people through the multimedia systems of the internet. Such confidential information in the images may be belong to the political, business, medical or military authorities. Protecting the privacy and integrity of these images in the era of the internet and multimedia technologies has drawn more attention by the research community. Image encryption is one of the most important tools to secure digital images from the unauthorized access and malicious manipulation. In this paper, a new digital image encryption method is proposed based on bit replacing technique, chaotic systems and DNA coding algorithm. It aims to protect the confidentiality and privacy of the digital images sent over unsecure open channels. Firstly, in this method each pixel of the image is converted to its corresponding binary sequence comprising of zeros and ones bits. Then, the zero bit is replaced by (1 and 0) bits and the one bit is replaced by (0 and 1) bits. Two different images are eventually generated by repeating consistently the replacing operation for all bits of the image pixels. Secondly, the generated images are encrypted using high dimensional chaotic systems based on the principle of permutation and diffusion processes in objective to vary the positions and values of the digital image pixels. Thirdly, the resultant encrypted images are encoded by adopting DNA algorithm rules and then these images are merged by exploiting DNA addition operation. Finally, the coded DNA images are decoded to obtain the output encrypted image. The numerical and visual simulation results confirm that the proposed method is sufficiently robust and secure against several known attacks in comparsion with the state-of-art approaches. Also, the conducted experiments show significant improvement in terms of entropy, correlation, differential, discrepancy metrics, key space and computational speed analysis performance parameters. To sum up, the proposed approach produced large secret key space of (2 747 ), a comparable differential analysis performance NPCR (99.61%) and UACI (34.61%) and passed all security and randomness tests.